Computer Vision-based Approaches, Datasets, and Applications of Smart Parking Systems: A Review - Hadi, Raad Ahmed; George, Loay Edwar; Ahmed, Zainab Jawad (Iraqi Journal of Science, 2024)
Nowadays, smart parking systems (SPS) represent one of the active research areas of intelligent transport systems (ITS). It is an interesting topic and attractive to researchers due to the difficult challenges that are needed to solve it. It enhances city life and plays an important role in reducing gas emissions, air pollution, and traffic congestion while improving the time override for drivers to easily allocate vacant parking lots. In this paper, we discuss and dedicate a review of how computer vision-based approaches can assist in providing wellness solutions for the occupancy of smart parking lots. In addition, we provide an overview of the most common standard datasets and some well-known applications of vacant smart parking lots.